Can the Linux kernel sustain 30 more years of growth? Toward mitigating bottlenecks in its development model - Tadokoro, David; Siqueira, Rodrigo; Meirelles, Paulo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
The Linux kernel, a cornerstone of modern computing and Free Software, forms the foundation of the GNU/Linux ecosystem and critical services like the Internet. Its development model integrates diverse workflows that extend beyond technical concerns. Despite its success, the project relies on key individuals and ad-hoc tools, raising sustainability and workforce renewal concerns. Moreover, known challenges within its development model remain underexplored in academic research. This paper presents ongoing efforts to develop taxonomies that describe these workflows, aiming to identify bottlenecks and guide the creation of Free Software tools to support the kernel long-term sustainability.